Prevalence of Vitamin - D Deficiency & Associated Factors Among the Medical Personnel of Medical College of Western Gujarat India - Kaliya, Dr Mehul; Rathod, Dr Mittal; Mahejbin, Dr Hirani; Shah, Dr Viral (International Journal of Innovative Research in Medical Science, 2022)
Vitamin D plays a major role in Calcium and Phosphate homeostasis and bone formation. Vitamin D deficiency can be a serious occurrence among healthy individuals, especially Medical Community, but Limited numbers of studies were found to know the vitamin D level in the medical community. As many clinicians and even nutritionists have not focused their attention on Vitamin D status may be due to it is assumed that exposure to sunlight > 15 minutes is sufficient to maintain an adequate level of vitamin D in the blood. Thus vitamin D deficiency can be a serious occurrence among healthy individuals, especially Medical Community. The present study was conducted with the objective of evaluating the prevalence Of Vitamin D deficiency among medical personnel in the medical college of western India. A cross-sectional study was conducted among 509 medical professionals of a medical college of western India irrespective of age, gender, college department, and medical conditions using a universal sample after ethical clearance from institutional IEC. Vitamin D level assessment was done by solid-phase enzyme-linked immunoassay (ELISA) based on the principle of competitive binding. Data entry and statistical analysis were done by Epi Info software. A total of 509 medical professionals participated in the study. Vitamin D Level was deficient in 45.97%, insufficient in 32.42%, and sufficient in 21.61%. Statistically, a significant association was found with less than an hour of sunlight exposure and Conclusions: Mean level of Vitamin D is 21.95 ng/ml which suggest insufficient level or near deficit level of vitamin D in the medical professional.